2015
DOI: 10.1002/poc.3508
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation on the Binding of a Cyanine Dye with Transferrin

Abstract: Transferrin (Tf) can control the level of free iron as iron-binding blood plasma glycoprotein in biological fluids. Tf has been exploited in the recent years on account of the potential function as a drug carrier targeting to tumor cells. Cyanine dyes have been widely studied as photosensitizers. The binding mechanism of Tf with 3, 3′-di(3-sulfopropyl)-4, 5, 4′, 5′-dibenzo-9-ethyl-thiacarbocyanine triethylammonium salt (ETC) was characterized at varying pHs and temperatures by fluorescence, UV-Vis absorption, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…When Δλ = 60 nm, a blue shift (from 281 to 276 nm) and a decrease in the synchronous fluorescence intensity of Trp are observed by increasing the concentration of the Fe complex, which indicated that the polarity around the Trp residues decreased and the hydrophobicity increased. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…When Δλ = 60 nm, a blue shift (from 281 to 276 nm) and a decrease in the synchronous fluorescence intensity of Trp are observed by increasing the concentration of the Fe complex, which indicated that the polarity around the Trp residues decreased and the hydrophobicity increased. [ 42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Binding of dye 52 occurs in the N-lobe of the protein and leads to an increase in the content of α-helices and increased hydrophobicity around tryptophan residues of hTf. Spectral-fluorescent and CD spectroscopies as well as molecular modeling have been used to study the binding mechanisms of dye 53 to hTf at various pH and temperatures [ 99 ]. As well as being structurally similar to 52 , trimethine cyanine 53 binds to hTf in the N-lobe with a high K eff ~10 7 L mol −1 ; quenching of intrinsic fluorescence of hTf by the dye is observed.…”
Section: Influence Of Interaction With Proteins and Other Biomolecule...mentioning
confidence: 99%